Impactul segregării şi diferenţierii asupra performanţelor şcolare ale elevilor din clasele 10-12. O analiză multinivel - Hatos, Adrian (Calitatea Vieții, 2008)
Though the effect of school social composition, with a focus on the consequences of social segregation and student body differentiation, on the students’ performances is internationally well documented, Romanian investigations on this topic are absent. My article assesses the impact of individual, classroom and school-level factors on GPAs of more than 1000 randomly selected students of grades 10 to 12, in 16 highschools from Oradea. Multilevel regression of school results proves that social background factors are effective at both individual and classroom level, while at the school-level, the most important is the institutionalized streaming embodied in highly specific types of high-schools.